Do Market-Based Tax Incentives Attract New Businesses? Evidence from the New Markets Tax Credit - Amanda Ross; Kaitlyn Wolf (European Regional Science Association (ERSA), 2014)
Policy makers at all levels of government believe that one of the key drivers of local economic growth is new businesses. Therefore, governments design policy with the intention of attracting businesses with the hopes that this will create future growth in struggling areas. Over the past few decades, the federal government has adjusted its approach to aid low-income communities to be based on market-based policies that encourage private investment in low-income communities. The underlying logic of these programs is that the best way to help local areas develop is to set up incentives for businesses at a local level to attract these drivers of growth to disadvantaged communities. By bringing new businesses and employment opportunities to a struggling area, there will be increased employment opportunities and the market will operate to reach an efficient outcome. In this paper, we use the New Market Tax Credit (NMTC) adopted in 2000 by the U.S. government to determine the effect of market-based, government-sponsored tax credits on the location decisions of new businesses. One issue when looking at the impact of business location decisions on growth is there is an inherent endogeneity issue, as entrepreneurs are likely to open their new establishment in growing areas. To address this endogeneity concern, we draw upon an eligibility cutoff in the NMTC to determine the impact of the tax credit on where businesses locate. By comparing census tracts with income levels that make the tract just eligible for the tax credit versus those that are just not eligible for the credit, we are able to obtain causal estimates. Using business location data from the Dun and Bradstreet MarketPlace Files, we find that in Metropolitan Statistical Areas in particular, the tax credit successfully incentivized businesses to locate in lower income census tracts. In particular, we found that these tax credits, aimed at increasing investment, had particularly strong effects on manufacturing. Our results suggest that these market-based tax incentives are having the intended effect of attracting new businesses to struggling areas. Our research fits into a growing literature on the impact of place-based tax programs on the development of local areas
Keywords: H25; J60; R23; R41; 330; Place-based programs; tax credits; regression discontinuity; entrepreneurship; agglomeration